The Relationship between the Nutritional Status of Adolescent Girls and the Incidence of Anemia: Literature Review: Hubungan Status Gizi Remaja Putri dengan Kejadian Anemia: Tinjauan Pustaka - Isti Sulistyana Djati; Sri Achadi Nugraheni; Ayun Sriatmi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Nutritional status is an indicator of body condition that is influenced by diet and nutrient utilization. Poor nutrient intake in adolescent girls has the potential to cause anemia where women are more susceptible to micronutrient deficiencies. WHO reports that 30% of women aged 15-49 years are anemic, with the highest prevalence in adolescents 15-19 years. The problem of anemia in adolescent girls has not been resolved, with low adherence to iron supplementation programs and poor nutritional knowledge. Methods: This study used a systematic literature review following the PRISMA method. Data were searched in several sources, including Scopus, PubMed, and Google Scholar, with the keywords “Nutritional status of adolescent girls” and “Anemia in adolescent girls.” The search process started in October 2024, focusing on relevant literature on nutritional status and anemia in adolescent girls and resulted in 20 articles used in this study. Results: Based on the articles that have been extracted and analyzed, 5 research articles showed an association between nutritional status and the incidence of anemia in adolescent girls, and 6 other articles stated that there was no association between nutritional status and the incidence of anemia in adolescent girls. Conclusion: The incidence of anemia in adolescent girls is generally caused by iron deficiency, due to irregular eating patterns, and consumption of junk food. In addition, it can also be caused by lack of knowledge, parents' income, mother's education, protein intake, vitamin C intake, breakfast habits, genetic factors, history of infectious diseases, and menstrual conditions. KEYWORDS: Nutritional Status of Adolescent Girls; Incidence of Anemia; Anemia in Adolescent Girls;